2009
DOI: 10.1242/dmm.001065
|View full text |Cite
|
Sign up to set email alerts
|

miR-23regulation of lamin B1 is crucial for oligodendrocyte development and myelination

Abstract: SUMMARYDuplication of the gene encoding lamin B1 (LMNB1) with increased mRNA and protein levels has been shown to cause severe myelin loss in the brains of adult-onset autosomal dominant leukodystrophy patients. Similar to many neurodegenerative disorders, patients with adult-onset autosomal dominant leukodystrophy are phenotypically normal until adulthood and the defect is specific to the central nervous system despite the ubiquitous expression pattern of lamin B1. We set out to dissect the molecular mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
188
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(200 citation statements)
references
References 53 publications
8
188
1
Order By: Relevance
“…For data normalization three different housekeeping genes (ACTB, LMNB1, PGK1) were utilized as endogenous controls (Figure 3), because housekeeping genes themselves can be targeted by miRNAs (Online Supplementary Table S6). For example, normalization of the measurements for SPARC and IRF2 using LMNB1, known to be targeted by miR-23a, 20 might lead to misinterpretation of results if compared to normalization with the other housekeeping genes ( Figure 3, open symbols; Online Supplementary Table S8).…”
Section: Validation Of Target Genes By Quantitative Reverse Transcripmentioning
confidence: 99%
“…For data normalization three different housekeeping genes (ACTB, LMNB1, PGK1) were utilized as endogenous controls (Figure 3), because housekeeping genes themselves can be targeted by miRNAs (Online Supplementary Table S6). For example, normalization of the measurements for SPARC and IRF2 using LMNB1, known to be targeted by miR-23a, 20 might lead to misinterpretation of results if compared to normalization with the other housekeeping genes ( Figure 3, open symbols; Online Supplementary Table S8).…”
Section: Validation Of Target Genes By Quantitative Reverse Transcripmentioning
confidence: 99%
“…We have previously shown that miR-23 overexpression enhances OL maturation in an established culture system (11). In addition, miR-23a and miR-23b are both up-regulated in OL under differentiation conditions compared with progenitor status under proliferation conditions (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…The repression of PTEN and enhancement of 2700046G09Rik by miR23a were validated by mutagenizing their respective miR-23a binding elements (Fig. S5 B-D) miR-23 exhibits a gradually increased expression pattern during postnatal development (11), and the true direct target genes of miR-23a should display expression patterns correlating with miR-23a expression. Indeed, the protein levels of PTEN display a gradual decrease from postnatal day 1 to 10 months of age (Fig.…”
Section: Overexpression Of Mir-23a Leads To Enhanced Myelination In Thementioning
confidence: 95%
See 1 more Smart Citation
“…(2013) provided new mechanisms of lamin B1 regulation, implicating miR‐23a (Lin & Fu, 2009; Lin et al., 2013). They first demonstrated that lamin B1 expression was developmentally regulated as the protein decreased in the mouse brain from birth to 300 days of age, while miR‐23a levels progressively increased in parallel.…”
Section: Mirnas In Hereditary Laminopathiesmentioning
confidence: 99%